Studies on thecorrelationbetweenthesoil microbiology and KautskyparametersK1 andK2 of thechlorophyllfluorescencedynamics ofwinter cropsin early spring - Nowick, Wolfgang; Nowick, Henry (Видавництво Львівської політехніки, 2013)
Measurement of chlorophyll fluorescence dynamics (CFD) and the determination of Kautsky parameters K1 and K2 is a sensitive method for the determination of plant vitality. In general, a plant is considered the healthier and more vital, the larger the parameters K1 and K2 are. In early spring is the question of how cultures have survived the winter period and what factors have made it impact, of particular interest because the agronomist must decide on the further applications of fertilizers and plant protection in this period. Измерение динамики флуоресценции хлорофилла (CFD) и определение параметров Эффекта Каутского К1 и К2 является чувствительным методом для определения степени жизнеспособности растения. Как правило, чем выше параметры K1 и K, тем активнее протекают процессы в клетках растения.Ранней весной у аграриев всегда чрезвычайно актуален вопрос, как растение перенесло зимний период и какие факторы повлияли на его состояние сейчас. Эта информация позволяет определить, какие удобрения и средства защиты должны применяться в дальнейшем.